Dm Methodology for Automating Technology System in Water Treatment Plants - Oddershede-Herrera, A; Quezada-Llanca, L; Macuada-Silva, C (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper proposes a methodology to support decision making for improving the efficiency in processes and upgrading the technological standard of drinking water treatment (WT) and wastewater treatment (WWT) plants. In this regard, it should be noted that progressively more requirements are required in terms of environmental and quality of service. At present, the industry is adopting new technologies for its processes and there is confidence that this is a way to improve their function. There is concern about automatism and tele controlled infrastructure requirements, the main critical factors for renewing infrastructure and planning methodology. Thus, it is necessary to determine the current level of technological system of WT and WWT plants and generate actions to make improvements in those plants showing poor quality of service. A case study has been carry out in a main sanitary company in Chile with the purpose to identify priority plants that must improve its technological standard. It has been considered the technological systems that are indispensable in the process. With empirical data, using multicriteria approach, expert opinions and combining scoring method with the Analytic Hierarchy Process (AHP) it was possible to obtain a plant ranking for the problem in study. © 2018 IEEE.